Atividade acaricida e inibição da acetilcolinesterase por terpenos em Rhipicephalus (Boophilus) microplus - CARDOSO, Alana Dos Santos (2019)
The tick Rhipicephalus (Boophilus) microplus is the most impacting hematophagous ectoparasite in Brazilian cattle. Their control is generally made with synthetic chemical compounds. However, inadequate handling and indiscriminate use of acaricides has accelerated the selection of ticks resistant to commercially available active ingredients. Terpenes have become a promising alternative to the use of synthetic compounds to control R. microplus, but the mechanism of action of these compounds is still controversial. Inhibition of the enzyme acetylcholinesterase (AChE) is a known mechanism of action of several acaricides. However little has been explored about the action of terpenes in AChEs. The objective of this work was to evaluate the acaricides action of terpenes, as well as their inhibitory potential in AChE, using resistant and sensitive strain of R. microplus. R. microplus larvae were macerated in 100 mM sodium phosphate buffer; pH 7.0; 0.5% v / v triton X-100; containing protease inhibitors. After thirty minutes, the suspension was centrifuged at 15000x g, 4 °C for 30 minutes. The supernatant was called enzyme extract and used as a source of AChE. AChE activity in the enzyme extract was verified as well as the inhibition of said enzyme by terpenes. Additionally, the acaricides action of terpenes on R. microplus larvae was evaluated. Among the terpenes used, p-cymene, thymol, carvacrol and citral presented acaricide activity with LC50 of 1.75, 1.54, 1.41 and 0.38 mg.mL-1 for susceptible strain and LC50 of 1.40. , 1.81, 1.10 and 1.13 mg.mL-1 for the resistant strain, respectively. Thymol and carvacrol inhibited AChE of susceptible strain larvae with IC50 of 0.93 and 0.04 mg.mL-1, respectively. The IC50 exhibited by eucalyptol, carvacrol and thymol for AChE of resistant strain larvae were 0.36, 0.28 and 0.13 mg.mL-1, respectively. This was the first study to investigate the action of terpenes on susceptible and resistant R. microplus AChE. For some terpenes, the positive correlation between acaricide activity and AChE inhibition suggests inhibition of this enzyme as a mechanism of action. This study contributes to the understanding of the mechanism of action of terpenes, supporting subsequent studies on the use of these products as acaricides.